The Conceptualization of Visual and Multimodal Metaphors in Iraqi Newspaper Cartoons (Journal of Misan Researches, 2025)
The current study explores the investigation of visual/ pictorial and multimodal metaphors in Iraqi newspaper cartoons. Four approaches were adopted in this study; namely, Lakoff and Johnson’s (1980) Conceptual Metaphor Theory to verbalize the materials of the sampled cartoons, Forceville’s (1996), Šorm and Steen’s (2018) VISMIP to recognize the visual/ pictorial metaphors, and Sobrino’s (2017) approach to investigate the multimodal modes of metaphors. Fifty-three cartoons, which were drawn by different cartoonists and published in the Iraqi local newspapers, were selected and sample for this study. The sampled cartoons addressed different issues to shed light on the negative and satirical effects of the daily socio-political and economic issues. The findings revealed that the visual and verbal modes are cued to conceptualize different topics and themes relate to the Iraqi affairs in the Iraqi newspaper cartoons using different source and target domains in addition to visualizing the verbal conventional metaphors. In conclusion, the Iraqi newspaper cartoons showed the metaphorical conceptualizations of different socio-political and economic issues by adopting different secondary subjects (source domains) in verbal and visual modes.